HUBUNGAN SELF-EFFICACY DENGAN PERILAKU CARING PERAWAT DI RAWAT INAP RSUD DR.DRAJAT PRAWIRANEGARA KOTA SERANG BANTEN - Siregar, Tatiana (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Standards of nursing care are the basis for professional nursing personnel. In the application of nursing care, one of the influences is the caring behavior of nurses. Caring behavior integrated with scientific knowledge can improve individual health. the component that influences caring behavior is self-efficacy. Nurses with high self-efficacy affect caring and caring attitudes when carrying out nursing care. This research method is quantitative descriptive analytic using cross sectional analysis approach. Collecting data in this study using purposive sampling method using a questionnaire. Sampling technique of 79 respondents. The questionnaires used were the General Self Efficacy Scale (GES) with 10 statements and the Caring Behaviors Assessment Tool with 62 statements. The results of statistical tests showed that nurses' self-efficacy was low as many as 45 respondents (57%) and nurses' caring behavior was categorized as low with 42 respondents (53.2%). Based on the results of the chi-square test, it shows that there is a significant relationship between self-efficacy and caring behavior of nurses with p value = 0.037 (p < 0.05). It can be concluded that self-efficacy with caring behavior of nurses in inpatient RSUD Dr. Drajat Prawiranegara Serang City. Self-efficacy of nurses can be increased again so that caring behavior can also increase.